Metal-doped and microstructure-regulated spherical lithium iron phosphate material and preparation method thereof
By introducing Ti and V bimetal doping and surfactant and carbon source composite layer into lithium iron phosphate materials, the problem of poor discharge performance of lithium iron phosphate materials in lithium batteries is solved, and high compaction density and excellent Electrochemical properties, and reduce production costs and energy consumption, are suitable for industrial production.
Patent Information
- Application Number
- CN202411226762.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2025-01-03
AI Technical Summary
The existing lithium iron phosphate materials have problems such as low discharge voltage and poor low-temperature electrical performance in the application of lithium batteries. The existing process for preparing spherical lithium iron phosphate materials is complex and costly, and is not suitable for industrial mass production.
Using Ti and V bimetal doped lithium iron phosphate material, a composite carbon layer clad material composed of surfactant and carbon source, combined with sand grinding and spray drying processes, a spherical iron phosphate with metal doping and microstructure regulation is formed. Lithium material improves its high compaction and discharge performance.
The high compaction density of lithium iron phosphate material has been achieved at least 2.42g/cm3, and the discharge energy of 0.1C reaches more than 159.5mAh/g. At the same time, the production cost and energy consumption are reduced, making it suitable for industrial mass production.
Smart Images

Figure CN119252878A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an electrode material, and in particular to a metal-doped and microstructure-regulated spherical lithium iron phosphate material and a preparation method thereof. Background Art
[0002] Lithium iron phosphate (LiFePO 4 Lithium iron phosphate (LFP) is widely used in lithium-ion power batteries and energy storage due to its high specific capacity, low price, non-toxicity and other advantages, and has become one of the most excellent green and environmentally friendly positive electrode materials. However, although lithium iron phosphate has better stability and safety than ternary materials due to its olivine structure, its own structural properties also make it difficult for lithium ions to be deintercalated in the crystal, resulting in low electronic conductivity and lithium ion conductivity characteristics, causing LFP to have problems such as low discharge voltage and poor low-temperature electrical properties, which also limits the widespread application of lithium iron phosphate.
[0003] The industrialization of lithium iron phosphate in the field of lithium batteries is mainly to further improve the energy density of lithium iron phosphate cathode materials. At present, lithium iron phosphate materials are generally required to have high compaction to reduce costs, from the previous 2.3g / cm 3 To date, 2.36 g / cm 3 As the industry develops, higher compaction may be required> 2.4g / cm 3 At the same time, certain requirements will be placed on the discharge specific capacity. Compared with traditional lithium iron phosphate materials, spherical lithium iron phosphate materials have higher energy density, relatively low internal resistance, and exhibit better electrochemical performance. Therefore, the preparation of spherical high-density lithium iron phosphate positive electrode materials will be one of the development points of industrialization.
[0004] The existing preparation technology generally achieves the purpose of spherical shape by hydrothermal synthesis or secondary treatment. For example, in the patent with publication number CN102479945, liquid phase coprecipitation method is used to prepare spherical lithium iron phosphate. Although the liquid phase method is conducive to morphology control, the liquid phase method has low yield, easy to produce impurity ions, high cost, and is not suitable for industrial mass production. For lithium battery materials, impurity ions are easy to precipitate, and metal deposition is produced. With the deposition, it not only seriously affects the battery performance but also has safety hazards. For example, in the patent with publication number CN101638226, it is necessary to sinter to generate lithium iron phosphate powder first, and then undergo secondary processing under high temperature and special environment to form spherical lithium iron phosphate powder. Secondary processing will increase energy consumption and industrialization cost in actual production. At the same time, special environment and secondary high temperature treatment will increase the risk of lithium iron phosphate producing impurities and are not conducive to the performance of lithium batteries. Therefore, a preparation method with simple process, which can be used for industrial mass production without increasing the number of calcination times, quality assurance, reduced energy consumption cost, and ensured that the lithium iron phosphate material is spherical is needed. Summary of the invention
[0005] Purpose of the invention: The first purpose of the present invention is to provide a spherical lithium iron phosphate material with metal doping and microstructure control, which has high compaction performance and excellent discharge performance; the second purpose of the present invention is to provide a method for preparing the above-mentioned spherical lithium iron phosphate material with low cost, simple process and mass production.
[0006] Technical solution: The metal-doped and microstructure-regulated spherical lithium iron phosphate material provided by the present invention is a lithium iron phosphate doped with Ti and V bimetallics and coated with a composite carbon layer; the composite carbon layer is carbonized from a surfactant and a carbon source.
[0007] Furthermore, the molar ratio of Ti to V is 1:0.5-2, preferably 1:1.
[0008] Furthermore, the mass ratio of the surfactant to the carbon source is 1:2.48-4.5, preferably 1:3-4.5.
[0009] Furthermore, the surfactant is one of active agents such as cetyltriethylammonium bromide (CATB), ethylenediaminetetraacetic acid (EDTA) or polyvinylpyrrolidone (PVP); the carbon source includes carbonizable materials such as sucrose, glucose, straw powder or Ketjen black.
[0010] The method for preparing the metal-doped and microstructure-layer-regulated spherical lithium iron phosphate material provided by the present invention comprises the following steps:
[0011] (1) adding a composite coating material consisting of a phosphorus iron source, a lithium source, a surfactant and a carbon source, and a dopant consisting of a Ti source and a V source into a solvent, stirring and dispersing, and preparing a slurry;
[0012] (2) The slurry is sand-milled and spray-dried to obtain a lithium iron phosphate precursor, which is then calcined and then air-flow-pulverized to obtain a spherical lithium iron phosphate material with metal doping and microstructure layer regulation.
[0013] Furthermore, in step (1), the ferrophosphorus source is a mixed ferric phosphate formed by compounding high iron-phosphorus ratio ferric phosphate and low iron-phosphorus ratio ferric phosphate in a mass ratio of 1:1-2, wherein the iron-phosphorus ratio of the high iron-phosphorus ratio ferric phosphate is 0.97-0.98, and the iron-phosphorus ratio of the low iron-phosphorus ratio ferric phosphate is 0.96-0.965; the compounded iron-phosphorus ratio of the mixed ferric phosphate is 0.968-0.972, and the specific surface area is 5-7m 2 / g, particle size D50<5μm;
[0014] Furthermore, in step (1), the lithium source is lithium carbonate, lithium hydroxide or lithium phosphate; the molar ratio of the lithium source to the ferrophosphorus source is 1:1.01-1.03; the Ti source is titanium dioxide, the mass of which is 0.2-1% of the mass of the ferrophosphorus source, and the V source is vanadium pentoxide; the total mass of the surfactant and the carbon source is 8-12% of the mass of the ferrophosphorus source.
[0015] Furthermore, in step (1), the solvent is pure water, and the solid content of the slurry is 40-41.5%.
[0016] Furthermore, in step (2), the particle size D50 of the lithium iron phosphate precursor obtained after spray drying is 20-30 μm; the particle size D50 of the metal-doped and microstructure layer-regulated spherical lithium iron phosphate positive electrode material obtained after airflow crushing is 1-2 μm.
[0017] Furthermore, in step (2), the calcination treatment conditions are: 2 Calcination in an atmosphere roller kiln at 700-850℃ for 19-21h.
[0018] Principle of the invention: On the one hand, a composite coating material composed of an active agent and a carbon source is introduced into lithium iron phosphate, and the material is uniformly coated on the surface of lithium iron phosphate through a sand milling process. The lithium iron phosphate precursor produced by spraying regulates the crystal morphology during the sintering process due to the action of a surfactant. At the same time, the surfactant used is an organic C-containing substance, which forms a dual carbon source state with the added carbon source after being carbonized by heat, further compensating for the carbon loss under high temperature, and effectively improving the situation of excessive carbon loss and incomplete coating caused by high-temperature calcination; on the other hand, Ti and V oxides are used for doping with dual high-valent metal cations to increase the Li vacancy concentration, reduce the Li-O bond energy, and improve the Li + The transmission rate is improved, and the ionic conductivity of lithium iron phosphate is improved. In addition, the bimetallic doping forms a larger lattice distortion on lithium iron phosphate, adjusts the lattice structure, increases the van der Waals force between the lattices, improves the compaction density of the lithium iron phosphate positive electrode material, and forms spherical high-compacted lithium iron phosphate while taking into account the advantages of electrochemical performance.
[0019] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: by doping with bimetallic Ti and V, and combining the surfactant and carbon source composite layer to regulate lithium iron phosphate, it can not only improve the high compaction performance of lithium iron phosphate, but also make its compaction density reach 2.42g / cm 3 In addition, it also improves the discharge performance of lithium iron phosphate, making its 0.1C discharge energy reach more than 159.5mAh / g. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the XRD pattern of the spherical lithium iron phosphate material prepared in Example 2;
[0021] Figure 2 This is a scanning electron microscope image of the spherical lithium iron phosphate material prepared in Example 2 after sintering;
[0022] Figure 3 This is a scanning electron microscope image of the finished spherical lithium iron phosphate material prepared in Example 2. DETAILED DESCRIPTION
[0023] The present invention is further described below in conjunction with specific embodiments and drawings.
[0024] Example 1: The metal-doped and microstructure-regulated lithium iron phosphate positive electrode material provided in this example is a lithium iron phosphate doped with Ti and V bimetallics and coated with a composite carbon layer; wherein the composite carbon layer is carbonized from surfactant CATB and carbon source sucrose.
[0025] The preparation method of the spherical lithium iron phosphate positive electrode material is as follows:
[0026] (1) The high iron-phosphorus ratio iron phosphate with an iron-phosphorus ratio of 0.97-0.98 and the low iron-phosphorus ratio iron phosphate with an iron-phosphorus ratio of 0.96-0.965 are compounded in a mass ratio of 1:1 to form an iron-phosphorus ratio of 0.97 and a specific surface area of 7m 2 / g, D50<5μm mixed iron phosphate, lithium carbonate, composite coating material, dopant are added into pure water, dispersed for 20min, and form a slurry with a solid content of 40.5%; wherein the molar ratio of lithium source to ferrophosphorus source is 1:1.02, the amount of composite coating material added is 8% of the mass of ferrophosphorus source, which is composed of CATB and sucrose in a mass ratio of 1:3, and the dopant is titanium dioxide and vanadium pentoxide in a molar ratio of 1:1, and the mass of titanium dioxide is 0.5% of the mass of ferrophosphorus source;
[0027] (2) The slurry was ground at a sand mill speed of 350 rpm for 120 min to obtain a slurry with a particle size D50 of 0.49 μm, and then transported to a spray dryer with an inlet air temperature of 260° C. and an atomizer wheel speed of 12000 rpm to obtain a lithium iron phosphate precursor with a particle size D50 of 25.7 μm;
[0028] (3) The lithium iron phosphate precursor is loaded into a double-layer graphite sagger and sent into a roller kiln for calcination at a temperature of 800° C. for 20 h. After the temperature in the cooling zone is less than 100° C., the lithium iron phosphate material is obtained by taking the precursor out of the kiln;
[0029] (4) The prepared lithium iron phosphate material is subjected to air flow pulverization to obtain a powder with a particle size D50 of 1.21 μm, thereby obtaining a spherical lithium iron phosphate positive electrode material.
[0030] Example 2: The metal-doped and microstructure-regulated lithium iron phosphate positive electrode material provided in this example is a lithium iron phosphate doped with Ti and V bimetallics and coated with a composite carbon layer; wherein the composite carbon layer is carbonized by a surfactant EDTA and a carbon source sucrose.
[0031] The preparation method of the spherical lithium iron phosphate positive electrode material is as follows:
[0032] (1) The iron-phosphorus ratio of high iron-phosphorus ratio iron phosphate is 0.97-0.98 and the iron-phosphorus ratio of low iron-phosphorus ratio iron phosphate is 0.96-0.965 in a mass ratio of 1:1 to form an iron-phosphorus ratio of 0.968 and a specific surface area of 7m 2 / g, D50<5μm mixed iron phosphate, lithium carbonate and composite coating material, dopant are added into pure water, dispersed for 20min, and form a slurry with a solid content of 40.85%; wherein the molar ratio of lithium source to ferrophosphorus source is 1:1.03, the amount of composite coating material added is 10% of the mass of ferrophosphorus source, which is composed of EDTA and sucrose in a mass ratio of 1:3, and the dopant is titanium dioxide and vanadium pentoxide in a molar ratio of 1:1, and the mass of titanium dioxide is 0.5% of the mass of ferrophosphorus source;
[0033] (2) grinding the prepared slurry at a sand mill speed of 350 rpm for 120 min to obtain a slurry with a particle size D50 of 0.481 μm, and then conveying it to a spray dryer with an inlet air temperature of 260° C. and an atomizer wheel speed of 11500 rpm to obtain a lithium iron phosphate precursor with a particle size D50 of 28.6 μm;
[0034] (3) The prepared lithium iron phosphate precursor is loaded into a double-layer graphite sagger and sent into a roller kiln for roasting at a temperature of 780° C. for 20 h. After the temperature in the cooling zone is less than 100° C., the lithium iron phosphate material is taken out of the kiln;
[0035] (4) The prepared lithium iron phosphate material is subjected to air flow pulverization to obtain a powder with a particle size D50 of 1.15 μm, thereby obtaining a spherical lithium iron phosphate positive electrode material.
[0036] The lithium iron phosphate prepared in Example 2 was subjected to SEM and XRD analysis, and the results obtained are as follows: Figure 1-Figure 3 shown.
[0037] pass Figure 1 As shown in the XRD diagram, the prepared material is pure LFP phase without any impurities. At the same time, the sharp peak of LFP phase indicates good crystallinity. Figure 2 and Figure 3The SEM in the image shows that under the combined action of the surfactant and the carbon source, the surface of the lithium iron phosphate is evenly coated with a carbon layer. At the same time, due to the regulation of the lattice morphology by EDTA, the nucleation is promoted to generate spherical lithium iron phosphate with relatively uniform size. The material has good crystallinity and complete grains. This is mainly due to the dual effects of the active substance and the dopant. Ti occupies the Li position, increasing the Li vacancy concentration, while V occupies the Fe position, increasing the lattice distortion, reducing the Li-O bond energy, and further improving the Li + The transmission capacity is improved to enhance the electrical performance of LFP, and finally a small-sized spherical lithium iron phosphate positive electrode material is obtained through air flow crushing.
[0038] Example 3: The metal-doped and microstructure-regulated lithium iron phosphate positive electrode material provided in this example is a lithium iron phosphate doped with Ti and V bimetallics and coated with a composite carbon layer; wherein the composite carbon layer is carbonized from surfactant CATB and carbon source sucrose.
[0039] The preparation method of the spherical lithium iron phosphate positive electrode material is as follows:
[0040] (1) The iron-phosphorus ratio of high iron-phosphorus ratio iron phosphate is 0.97-0.98 and the iron-phosphorus ratio of low iron-phosphorus ratio iron phosphate is 0.96-0.965 in a mass ratio of 1:1 to form an iron-phosphorus ratio of 0.972 and a specific surface area of 6m 2 / g, D50<5μm mixed iron phosphate, lithium carbonate and composite coating material are added into pure water and dispersed for 20min to form a slurry with a solid content of 41.03%; wherein the molar ratio of lithium source to ferrophosphorus source is 1:1.02, the amount of composite coating material added is 8% of the mass of ferrophosphorus source, which is composed of CATB and sucrose in a mass ratio of 1:4, and the dopant is titanium dioxide and vanadium pentoxide in a molar ratio of 1:1, and the mass of titanium dioxide is 0.5% of the mass of ferrophosphorus source;
[0041] (2) grinding the prepared slurry at a sand mill speed of 350 rpm for 120 min to obtain a slurry with a particle size D50 of 0.476 μm, and then conveying it to a spray dryer with an inlet air temperature of 250° C. and an atomizer wheel speed of 12000 rpm to obtain a lithium iron phosphate precursor with a particle size D50 of 24.9 μm;
[0042] (3) The prepared lithium iron phosphate precursor is loaded into a double-layer graphite sagger and sent to a roller kiln for calcination at a temperature of 790° C. for 21 h. The lithium iron phosphate material is taken out of the kiln after the temperature in the cooling zone is less than 100° C.;
[0043] (4) The prepared lithium iron phosphate material is subjected to air flow pulverization to obtain a powder with a particle size D50 of 1.17 μm, thereby obtaining a spherical lithium iron phosphate positive electrode material.
[0044] Example 4: The metal-doped and microstructure-regulated lithium iron phosphate positive electrode material provided in this example is a lithium iron phosphate doped with Ti and V bimetallics and coated with a composite carbon layer; wherein the composite carbon layer is carbonized from a surfactant PVP and a carbon source glucose.
[0045] The preparation method of the spherical lithium iron phosphate positive electrode material is as follows:
[0046] (1) The iron-phosphorus ratio of high iron-phosphorus ratio iron phosphate is 0.97-0.98 and the iron-phosphorus ratio of low iron-phosphorus ratio iron phosphate is 0.96-0.965 in a mass ratio of 1:1 to form an iron-phosphorus ratio of 0.972 and a specific surface area of 6m 2 / g, D50<5μm mixed iron phosphate, lithium carbonate and composite coating material are added into pure water and dispersed for 20min to form a slurry with a solid content of 41.39%; wherein the molar ratio of lithium source to ferrophosphorus source is 1:1.03, the amount of composite coating material added is 12% of the mass of ferrophosphorus source, which is composed of PVP and glucose in a mass ratio of 1:4.5, and the dopant is titanium dioxide and vanadium pentoxide in a molar ratio of 1:1, and the mass of titanium dioxide is 0.5% of the mass of ferrophosphorus source;
[0047] (2) grinding the prepared slurry at a sand mill speed of 380 rpm for 150 min to obtain a slurry with a particle size D50 of 0.461 μm, and then conveying it to a spray dryer with an inlet air temperature of 250° C. and an atomizer wheel speed of 12000 rpm to obtain a lithium iron phosphate precursor with a particle size D50 of 24.6 μm;
[0048] (3) The prepared lithium iron phosphate precursor is loaded into a double-layer graphite sagger and sent into a roller kiln for roasting at a temperature of 820° C. for 20 h. After the temperature in the cooling zone is less than 100° C., the lithium iron phosphate material is taken out of the kiln;
[0049] (4) The prepared lithium iron phosphate material is subjected to air flow pulverization to obtain a powder with a particle size D50 of 1.24 μm, thereby obtaining a spherical lithium iron phosphate positive electrode material.
[0050] Comparative Example 1: The basic steps are the same as those of Example 2, except that the composite coating material uses only a single carbon source, and does not use an active agent, doping agent titanium dioxide and vanadium pentoxide. The specific steps are as follows:
[0051] The preparation method of lithium iron phosphate of Comparative Example 1 comprises the following steps:
[0052] (1) The high iron-phosphorus ratio iron phosphate with an iron-phosphorus ratio of 0.97-0.98 and the low iron-phosphorus ratio iron phosphate with an iron-phosphorus ratio of 0.96-0.965 were compounded in a mass ratio of 1:1 to form an iron-phosphorus ratio of 0.97±0.002 and a specific surface area of 6±1m 2 / g, D50<5μm mixed iron phosphate, lithium carbonate and composite carbon source are added into pure water and dispersed for 20min to form a slurry with a solid content of 40.87%; wherein the molar ratio of lithium source to ferrophosphorus source is 1:1.03, the single carbon source is sucrose, the addition amount is 10% of the mass of the ferrophosphorus source, and the dopant is titanium dioxide and vanadium pentoxide in a molar ratio of 1:1, and the mass of titanium dioxide is 0.5% of the mass of the ferrophosphorus source;
[0053] (2) grinding the prepared slurry at a sand mill speed of 380 rpm for 120 min to obtain a slurry with a particle size D50 of 0.465 μm, and then transporting it to a spray dryer with an inlet air temperature of 250° C. and an atomizer wheel speed of 12000 rpm to obtain a lithium iron phosphate precursor with a particle size D50 of 25.7 μm;
[0054] (3) The prepared lithium iron phosphate precursor is loaded into a double-layer graphite sagger and sent into a roller kiln for roasting at a temperature of 780° C. for 20 h. After the temperature in the cooling zone is less than 100° C., the lithium iron phosphate material is taken out of the kiln;
[0055] (4) The prepared lithium iron phosphate material is crushed to obtain a powder with a particle size D50 of 0.87 μm, thereby obtaining a lithium iron phosphate material.
[0056] Comparative Example 2: The basic steps are the same as those of Example 2. The composite coating material is made by carbonizing surfactant EDTA and sucrose. The difference is that a single dopant, titanium dioxide, is used.
[0057] The preparation method of lithium iron phosphate of Comparative Example 2 comprises the following steps:
[0058] (1) The high iron-phosphorus ratio iron phosphate with an iron-phosphorus ratio of 0.97-0.98 and the low iron-phosphorus ratio iron phosphate with an iron-phosphorus ratio of 0.96-0.965 were compounded in a mass ratio of 1:1 to form an iron-phosphorus ratio of 0.97±0.002 and a specific surface area of 6±1m 2 / g, D50<5μm mixed iron phosphate, lithium carbonate and composite carbon source are added into pure water and dispersed for 20min to form a slurry with a solid content of 40.69%; wherein the molar ratio of lithium source to ferrophosphorus source is 1:1.03, the amount of composite coating material added is 10% of the mass of ferrophosphorus source, which is composed of EDTA and sucrose in a mass ratio of 1:3, and a single dopant titanium dioxide is used, and the mass of titanium dioxide is 1.6% of the mass of ferrophosphorus source;
[0059] (2) grinding the prepared slurry at a sand mill speed of 380 rpm for 120 min to obtain a slurry with a particle size D50 of 0.465 μm, and then conveying it to a spray dryer with an inlet air temperature of 250° C. and an atomizer wheel speed of 12000 rpm to obtain a lithium iron phosphate precursor with a particle size D50 of 27.1 μm;
[0060] (3) The prepared lithium iron phosphate precursor is loaded into a double-layer graphite sagger and sent into a roller kiln for roasting at a temperature of 780° C. for 20 h. After the temperature in the cooling zone is less than 100° C., the lithium iron phosphate material is taken out of the kiln;
[0061] (4) The prepared lithium iron phosphate material is crushed to obtain a powder with a particle size D50 of 0.98 μm, thereby obtaining a lithium iron phosphate material.
[0062] The lithium iron phosphate materials prepared in Examples 1 to 4 and Comparative Examples 1 and 2 were tested for performance, and the results obtained are shown in Table 1 below.
[0063] As shown in Table 1, the lithium iron phosphate prepared by the preparation method of the present invention by forming a surface coating material with a surfactant and a carbon source and doping with metal cations can ensure the C content level and increase the compaction density of the finished lithium iron phosphate by ≥2.42 g / cm at the primary calcination temperature. 3 , the discharge performance is guaranteed at 159.5mAh / g.
[0064] When a single carbon source is used, the C content of the material in Comparative Example 1 is significantly reduced, and the particle size of the modified material without a surfactant is significantly reduced, resulting in high BET and electrical properties, which affects the electrical properties.
[0065] In addition, although the particle size of the material in Comparative Example 2, which uses a composite carbon source but only a single doping, is improved, there is no synergistic effect of the bimetallic cations on the lattice, and its discharge performance is less than 159 mAh / g, and the efficiency is low. Therefore, the synergistic effect of the surfactant-modified morphology and the dual doping on the lattice enables the lithium iron phosphate to exert higher electrical properties, and no by-product iron phosphide is produced.
[0066] Table 1 Test results of Example 1-Example 4 and Comparative Example 1 and Comparative Example 2
[0067]
Claims
1. A metal-doped and microstructure-controlled spherical lithium iron phosphate material, characterized in that: The outer surface of lithium iron phosphate doped with Ti and V bimetallic is coated with a composite carbon layer; the composite carbon layer is carbonized from a surfactant and a carbon source.
2. The spherical lithium iron phosphate material according to claim 1, characterized in that: The molar ratio of Ti to V is 1:0.5-2.
3. The spherical lithium iron phosphate material according to claim 1, characterized in that: The mass ratio of the surfactant to the carbon source is 1:2.48-4.
5.
4. The spherical lithium iron phosphate material according to claim 1, characterized in that: The surfactant is hexadecyltriethylammonium bromide, ethylenediaminetetraacetic acid or polyvinylpyrrolidone.
5. The spherical lithium iron phosphate material according to claim 1, characterized in that: The carbon source includes sucrose, glucose, straw powder or Ketjen black.
6. A method for preparing the spherical lithium iron phosphate material according to claim 1, characterized in that: The following steps are involved: (1) adding a composite coating material consisting of a phosphorus iron source, a lithium source, a surfactant and a carbon source, and a dopant consisting of a Ti source and a V source into a solvent, stirring and dispersing, and preparing a slurry; (2) The slurry is sand-milled and spray-dried to obtain a lithium iron phosphate precursor, which is then calcined and then air-flow-pulverized to obtain a spherical lithium iron phosphate material with metal doping and microstructure layer regulation.
7. The preparation method according to claim 6, characterized in that: In step (1), the molar ratio of the lithium source to the ferrophosphorus source is 1:1.01-1.03; the Ti source is titanium dioxide, the mass of which is 0.2-1% of the mass of the ferrophosphorus source; the V source is vanadium pentoxide; and the total mass of the surfactant and the carbon source is 8-12% of the mass of the ferrophosphorus source.
8. The preparation method according to claim 6, characterized in that: In step (1), the solvent is pure water, and the solid content of the slurry is 40-41.5%.
9. The preparation method according to claim 6, characterized in that: In step (2), the particle size D50 of the lithium iron phosphate precursor obtained after spray drying is 20-30 μm; the particle size D50 of the metal-doped and microstructure layer-controlled spherical lithium iron phosphate material obtained after airflow pulverization is 1-2 μm.
10. The preparation method according to claim 6, characterized in that: In step (2), the calcination treatment conditions are: calcination in a roller kiln in a N2 atmosphere at 700-850°C for 19-21 hours.
Citation Information
Cited By
Secondary sintering process method for improving compaction density of lithium iron phosphate and application of secondary sintering process method
CN121317679A
